اردو زبان میں ترجمہ نگاری کے ارتقائی مراحل: EVOLUTIONARY STAGES OF TRANSLATION IN THE URDU LANGUAGE (Al-Aasar, 2025)
The tradition of translation in Urdu literature is an ancient and significant aspect that not only serves as a bridge between different cultures and languages but also plays a crucial role in the development of literature. The inception of translation in Urdu occurred under the influence of various civilizations and languages, with translations made from Eastern languages such as Persian, Arabic, Sanskrit, and Brij Bhasha into Urdu. During the Mughal era, translations were made from different languages into Persian, and during Akbar's reign, many important books were translated from Sanskrit into Persian. The practice of translation in Urdu began in the latter half of the fifteenth century, and its evolution took place over different historical periods, with various translations strengthening the intellectual and cultural foundations of Urdu literature. Translation in Urdu has faced numerous challenges and issues over time, especially in translating poetry, where accurately conveying complex concepts such as imagination, allegory, symbolism, and metaphors has been difficult. However, in different periods, translators managed to handle this art skillfully, such as Shah Waliullah and other scholars who translated the Quran into Urdu, and translations of various Persian and Arabic works into Urdu provided new dimensions to Urdu literature. This tradition is still alive today, and through translation, not only is literature created, but various cultural and religious messages are also transferred into new languages. The tradition of translation in Urdu continues to be a strong link between literature, culture, and languages, helping to create a robust connection between them.